"It is easier for me to shoot up": stigma, abandonment, and why HIV-positive drug users in Russia fail to link to HIV care. Issue 5 (4th May 2017) - Kiriazova, Tetiana; Lunze, Karsten; Raj, Anita; Bushara, Natalia; Blokhina, Elena; Krupitsky, Evgeny; Bridden, Carly; Lioznov, Dmitry; Samet, Jeffrey H.; Gifford, Allen L.
ABSTRACT: Many HIV-positive people who inject drugs (PWID) globally are not receiving HIV care. This represents a major challenge among key populations to end the global HIV epidemic. This qualitative study explored the process and associated barriers of linking HIV-positive PWID who are in addiction treatment to HIV care in St. Petersburg, Russia. We conducted three focus groups and seven semi-structured interviews with participants in the LINC ("Linking Infectious and Narcology Care") project at addiction and HIV hospitals in St. Petersburg. The sample consisted of 25 HIV-infected patients with opioid dependence and seven health-care providers, including addiction and infectious disease physicians and case managers. A variety of intertwining factors influence effective engagement of PWID with HIV treatment. Stigma, problematic patient–provider relationships, and fragmented health care were the main challenges for HIV care initiation by PWID, which were further exacerbated by injection drug use. Effective linkage of PWID to HIV care requires acknowledging and addressing stigma's role and different perspectives of patients and providers.